Research Mapping of Asset and Liability Management Strategy in Islamic Banking - Khuluddiyah, Zulaikhatul (Jurnal Bisnis, Manajemen, dan Ekonomi, 2024)
This study aims to map asset and liability management (ALMA) strategies in Islamic banking through a bibliometric approach using VOSviewer software and literature review methods. By analyzing 151 publications from 2004 to 2024, this study explores key themes in ALMA such as profitability, liquidity, and risk, and their relationship with indicators such as economic value added (EVA) and return on equity (ROE). The findings show a progression from a siloed approach towards a more comprehensive strategic integration to enhance the competitiveness of Islamic banks. The results also identify research gaps, such as the lack of comparative studies between Islamic and conventional banks, limited studies on new Islamic financial instruments such as sukuk, and the lack of utilization of digital technology in supporting ALMA strategies. This study makes an important contribution to the academic literature and industry practice, with recommendations to focus on the integration of technological innovation and shariahbased product diversification in the management of ALMA. This study uses secondary data that is analyzed qualitatively and quantitatively to provide deeper insights.